2021
DOI: 10.1126/sciadv.abi6856
|View full text |Cite
|
Sign up to set email alerts
|

Rare genetic variability in human drug target genes modulates drug response and can guide precision medicine

Abstract: Interindividual variability in drug response constitutes a major concern in pharmacotherapy. While polymorphisms in genes involved in drug disposition have been extensively studied, drug target variability remains underappreciated. By mapping the genomic variability of all human drug target genes onto high-resolution crystal structures of drug target complexes, we identified 1094 variants localized within 6 Å of drug-binding pockets and directly affecting their geometry, topology, or physicochemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In G‐protein coupled receptors (GPCRs), which constitute the targets of 34% of approved drugs, sequencing has identified 14 192 missense variants, covering approximately 25% of all nucleotide positions across the entire GPCRome 40 . Further drug target sequencing projects showed that rare variants are predominant also in other PD genes with around 800 000 genetic variants being identified across all FDA‐approved drug targets (98.1% of which were rare with MAF < 1%) 41,42,45 …”
Section: Pharmacogenomic Variability Beyond Well‐characterized Polymo...mentioning
confidence: 99%
See 1 more Smart Citation
“…In G‐protein coupled receptors (GPCRs), which constitute the targets of 34% of approved drugs, sequencing has identified 14 192 missense variants, covering approximately 25% of all nucleotide positions across the entire GPCRome 40 . Further drug target sequencing projects showed that rare variants are predominant also in other PD genes with around 800 000 genetic variants being identified across all FDA‐approved drug targets (98.1% of which were rare with MAF < 1%) 41,42,45 …”
Section: Pharmacogenomic Variability Beyond Well‐characterized Polymo...mentioning
confidence: 99%
“… 40 Further drug target sequencing projects showed that rare variants are predominant also in other PD genes with around 800 000 genetic variants being identified across all FDA‐approved drug targets (98.1% of which were rare with MAF < 1%). 41 , 42 , 45 …”
Section: Pharmacogenomic Variability Beyond Well‐characterized Polymo...mentioning
confidence: 99%
“…[ 31 ] Specifically, the mutation in the drug‐binding pocket directly influences drug‐target interactions by modifying pocket geometry, topology, or physiochemical interactions. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…[31] Specifically, the mutation in the drug-binding pocket directly influences drug-target interactions by modifying pocket geometry, topology, or physiochemical interactions. [32] For 044, currently undergoing phase II clinical trials, holds great promise as the first anti-metastatic drug. [26] However, the emergence of resistance is a likely eventuality.…”
Section: The Prediction Of Drug Resistance Mutationmentioning
confidence: 99%
“…1% and 0.1% of analyzed probesets comprising genes, pseudogenes and precursor microRNAs (n = 32,232) were significantly correlated (absolute r S > 0.04) to SLC10A1 mRNA expression (measured by qPCR) and NTCP protein levels, respectively. Then, we investigated whether pharmacogenes (n = 344) [63], target genes (n = 564) [64] or precursor miRNAs (n = 1372) were correlated with NTCP expression. The significantly correlated genes (adjusted p < 0.05, absolute r S > 0.4) predominately belonged to the pharmacogene group (SLC10A1 mRNA = 5.81%; NTCP protein = 1.45%; Figure 6A).…”
Section: Genome-wide Expression Correlation Analysis and Gene Set Enr...mentioning
confidence: 99%